The Effect of Empowerment Program on Family Members’ Caring Behaviors for Patients with Hypertension - Kingsangval, Pianghathai; Jewpattanakul, Yupa; Nakagasien, Piyatida (Nursing Science Journal of Thailand, 2024)
Purpose: To study the effects of a family member empowerment program on family members’ caring behaviors for patients with hypertension. Design: Quasi-experimental. Methods: The sample was consisted of 86 family members mainly responsible for the care of patients with hypertension living in communities, Bangkok, divided into experimental and control groups with 43 each. The experimental group received the empowerment program applied from Gibson’s empowerment concept, which contained the following activities: discovering the reality by exchanging experiences of care among caregivers, obtaining advices through handbook and short video clips about care for patients with hypertension, and receiving phone calls encouraging proper decision making and practices in care with respect to dietary intake, exercise, medication adherence, stress relief, and keeping appointments. Moreover, 6 short messages and 4 callings were offered to the experimental group for maintaining efficient practice. The control group received home visit and general health education. Caring behaviors were assessed before and 8 weeks after the program. Data were collected by using a demographic questionnaire, a questionnaire on family members’ perceived empowerment, and a questionnaire on caring behavior for patients with hypertension. Data were analyzed using independent t-test and paired t-test. Main findings: After participating in the program, the experimental group had significantly higher mean scores of caring behaviors for patients with hypertension than the control group (t(84) = 10.75, p < .001). Compared to means scores of family members’ caring behaviors for patients with hypertension in the experimental group prior to the program, the scores after the program were significantly higher (t(42) = 10.28, p < .001). Conclusion and recommendations: The empowerment program was effective in improving family members’ caring behaviors for patients with hypertension. An empowerment program should be designed for both patients with hypertension and their family members. Moreover, the program should be adapted for family members in caring for patients with others chronic diseases.